Improvement on robotic running foot for footwear testing - Lianto, Alfons Sebastian (2019)
Every footwear manufacturers is competing to make the best footwear in term of cushioning, flexibility, durability, etc. To create the best footwear, the new model of the footwear needs to be tested before it is launched to the market. One way to test the footwear characteristic is through mechanical device. Mechanical device for footwear testing uses mechanical principle to replicate the motions of the human foot during gait. The number of replicated motions depends on the degrees of freedom (DOF) of the device. The more DOF means the robot can replicate more motions. The current mechanical devices for footwear testing has up to six degrees of freedom which can replicate movement such as ankle joint, toes joint and leg joint. However, six degrees of freedom on mechanical device for footwear testing are still unable to perfectly replicate the human gait. One lacking motion of current footwear testing mechanical devices is the inversion and eversion of the forefoot. These motions are important to distribute the Ground Reaction Force and offer stability during gait. The objective of this project is to design an additional mechanism that replicates the inversion and eversion of the forefoot to the current Robotic Running Foot developed by Nguyen et al. In this project, possible mechanisms are sourced and sketched before the best and most feasible mechanism is selected. The selection process includes the process of reviewing the advantages and disadvantages of the sketches. Once the best sketch is selected, this sketch is developed using Computer Aided Design (CAD) and analyized using SolidWorks Simulation with detailed dimension and material. Subsequently, the final design is validated by creating the 3D printed mock-up. These processes are done to ensure the design functionality of the result is achieved. As a result, a design to add a new degree of freedom that can replicate the inversion and eversion of the human forefoot is made. This new degree of freedom uses 2 compression springs with adjustable spring strength to replicate the flexibility of the forefoot.